If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(10 + x) = 3 (10 * 3 + x * 3) = 3 (30 + 3x) = 3 Solving 30 + 3x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 3x = 3 + -30 Combine like terms: 30 + -30 = 0 0 + 3x = 3 + -30 3x = 3 + -30 Combine like terms: 3 + -30 = -27 3x = -27 Divide each side by '3'. x = -9 Simplifying x = -9
| 6x+7x+8=36 | | x-41=-6 | | 12x-3-2x=0 | | 6/7a=16 | | 6x+3-9x=12-15x+12x-9 | | 4a^2+12a-27=0 | | (2/3)x=-9 | | 1/3d(60-t) | | -2(-7+3x)=-22 | | 3(2c-1)-2=2c+3 | | 6(10-3x)=10-8x | | m-20=10 | | 3/14N=3/16 | | (4t+5)(3t+10)=0 | | -8+3x=-4x+55 | | -2(x+1)+x=7-4x | | x-[5+3x-[5x-(6+x)]]=-3 | | 2X=4/15 | | 6x+1=3x+4 | | y+15=-30 | | x-2x+12-3x=-5(x-2)+2 | | 8+3n=-2a+24 | | 2x-6-8=0 | | 4-2x=8+.5x | | -4x-3=6x-123 | | -0x+10-3x=-5(x-2)+2 | | x+22+3x=-19-3x-22 | | -2x+9-3x=-5(x-2)+2 | | -2x+12-3x=-5(x-2)+0 | | -2x+12-3x=5(x-2)+2 | | 4+3x=7x-24 | | 3(s+2)-(2s-3)=5 |